Thermoregulatory comfort properties of sports jersey fabric: a review / Suraya Ahmad Suhaimi ... [et al.] - Ahmad Suhaimi, Suraya; Ruznan, Wan Syazehan; Raja Hussain, Raja Nurul Jannat; Mohd Nor, Mohd Azlin; Ahmad, Mohd Rozi (UiTM Press, 2025)
This paper explores the thermoregulatory properties of sports jersey fabrics. This review aims to analyse the influence of material composition, fabric structures, and design features on thermal comfort and athletic performance. Investigation of natural and synthetic fibres, and recent innovations in regenerated and microfibres forms the foundation of the review. Key findings include the significant impact of synthetic fibres, particularly polyester, nylon, and spandex, enhancing performance through moisture-wicking properties. Knitted fabrics outperform woven structures in flexibility and moisture transport. Coolmax® and Tencel™ improve athlete comfort through moisturewicking properties. Thermal comfort and moisture management improved by yarn combinations in multi-layer clothing systems. The review emphasizes the importance of design features that combine aesthetics and functionality, essential for enhancing athletic performance. Although the review covers material and structural factors, it lacks a thorough technical analysis of heat and moisture transfer mechanisms in various fabric structures and fibre blends. Comprehensive analysis may improve understanding of fabric engineering strategies to enhance thermoregulatory comfort. The paper discusses the evolution of sportswear design, multi-layer systems, performance, and comfort, enhanced temperature regulation. The review outlines current challenges, presenting perspectives for future advancements in sports jersey fabrics aiming to improve thermoregulatory performance across various environmental conditions.